Attempt to Harvest a Sufficient Number of Mononuclear Cells in an Appropriate Blood Product Volume By Modification of the Default Apheresis Setting. Issue 5 (21st July 2017) - Tanaka, Yumi; Ohishi, Kohshi; Sawai, Toshiki; Iwasaki, Hitoshi; Kageyama, Shinichi; Masuya, Masahiro; Matsumoto, Takeshi; Tanigawa, Takashi; Wada, Hideo; Shiku, Hiroshi; Ito, Masaaki; Katayama, Naoyuki
Abstract: To harvest for T cell therapy, a 1.6‐fold higher number of CD3 + T cells was collected with MNC mode ( N = 10) compared with Auto PBSC mode ( N = 5) in COBE Spectra cell separator, but the blood product volume was increased by 3.5‐fold. For therapeutic angiogenesis therapy, apheresis was initially performed using Auto PBSC mode ( N = 4) to fine tune the blood product volume to omit cell concentration, but the collected number of mononuclear cells was lower than expected. However, an increase of the harvest cycle number from 3.8 ± 0.5 to 7.4 ± 2.0 cycles ( N = 19) resulted in a 2.1‐fold higher number of collected mononuclear cells (8.7 ± 4.1 × 10 9 vs. 4.1 ± 1.0 × 10 9 cells, P < 0.05). The increase in blood product volume by this modification appeared to be lower than that expected with MNC mode. These data show that optimal harvesting can be achieved by modification of default collection settings.